Preparation and characterisation of biocompatible polyethersulfone-based hollow fibre membrane for haemodialysis application - Sumarni Mansur, 1990-, author; Mohd. Hafiz Dzarfan Othman, supervisor; Fatmawati Kamal, supervisor; Fakulti Kejuruteraan Kimia dan Kejuruteraan Tenaga (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Falsafah) - Universiti Teknologi Malaysia, 2016